Respuesta :
You need to multiply x + 2y = 13 by -4 then the -4 and +4 will cancel each other out then you solve the rest of the equation.
y= zero
using the process of substitution I had this...
4( -2y +13) +8y = -9
distribution -8y +52 -8y= -9
so -8y+8y =0
you end up having zero for y no matter what the subtraction of 52 was, because anything divided by zero is zero...
so if you already have the x value, your point is going to be an x-intercept
using the process of substitution I had this...
4( -2y +13) +8y = -9
distribution -8y +52 -8y= -9
so -8y+8y =0
you end up having zero for y no matter what the subtraction of 52 was, because anything divided by zero is zero...
so if you already have the x value, your point is going to be an x-intercept